Germination of Euphorbia Heterophylla L. and its Control in Cowpea (Vigna Unguiculata (L) walp). - O'Makinwa, Rufus Oyeniyi (Obafemi Awolowo University, 2014)
In order to understand the influence of temperature and light duration on the germination of Euphorbia heterophylla L., freshly harvested and pre-chilled seeds of the weed were incubated in an illuminated cooled incubator for varying light and temperature regimes. Their germination was observed daily for 10 days. In another study aimed at identifying the most effective herbicides and herbicide combination and time of application for the control of E. heterophylla, separate screenhouse and field trials were conducted. In both the screenhouse, and field trials, two rates each of alachlor, cyanazine, acifluorfen and metobromuron + metolachlor were applied at different times after planting to control the weed in two cowpea (Vigna unguiculata (L.) Walp.) cultivars (Ife brown and TVx 3236) .